Consumer Purchase Decision in The Malaysian Retail Market: A Study of RM 2 Stores - Majid, Muhammad; Ramli, Mohamad Faizal; Badyalina, Basri; Roslan, Azreen; Che Mohd Hashim, Azreen Jihan; Mohd Nadzri, Wan Nadiah (UUM Press, 2023)
This study aimed to investigate factors that influence consumer purchase decision in Malaysian single-priced stores, which are also popularly known as RM2 stores. The study considered six factors that could affect purchase decision in RM2 stores, namely, corporate social responsibility (CSR), sales promotion, social media marketing, perceived value, store environment, and service quality. A quantitative research methodology was employed through a survey using questionnaires administered to 550 customers of the RM2 stores. The data gathered was then analysed through SPSS method to calculate the validity and reliability of the measurement items and to verify the impact of six independent variables on purchase decision. Based on the results, CSR, sales promotion, perceived value, and service quality had significant positive effects on purchase decision, while social media marketing and store environment proved to be insignificant. Among all the factors, perceived value had the strongest influence on purchase decision. The findings are important in assisting RM2 store retailers to understand the factors that affect consumer purchase decision which could help in improving sales. This study complements the current literature and addresses existing research gaps with regard to the linkages between factors that influence consumer purchase decision in Malaysian single-priced stores.